Degenerative Spondylolisthesis of Lumbarized S1-S2 Vertebrae: A Case Report - Deepak Kumar Singh; Kshitij Sinha; Rakesh Kumar Singh; Vipin Kumar Chand; Arun Kumar Singh (Indian Journal of Neurosurgery)
Introduction Degenerative spondylolisthesis (DS) is usually seen at lumbo-sacral region. Lumbarization of S1 is seen in less than 2% of the population and to have spondylolisthesis in this segment is even rarer. The purpose is to report a rare case of DS at S1-S2 level.